Policy Analysis of Food Security in North Sumatra Province - Anggi Puspita Herdianty (ProBisnis : Jurnal Manajemen, 2021)
Food is a basic need for humans to be able to sustain life and therefore adequate food for everyone at all times is a human right that deserves to be fulfilled. Based on this fact, the problem of meeting food needs for the entire population at any time in an area becomes the main target of food policy for the government of a country. Indonesia as a country with a large population faces very complex challenges in meeting the food needs of its population. Therefore, the policy of strengthening food security becomes a central issue in development and becomes the main focus in agricultural development. The purpose of this study is to conduct an analysis of food security policies and to find out how to improve food security in the province of North Sumatra, The method used in this research is to use a quantitative descriptive approach. North Sumatra as one of the rice producing areas has a fluctuating level of rice production from time to time. The condition of harvested areas in North Sumatra is increasingly threatened with the increasing number of residents every year which causes the demand for residential land and infrastructure to increase. In addition to harvested area, consumption per capita of the population of North Sumatra is also a factor that affects food security in North Sumatra. The condition of harvested areas in North Sumatra is increasingly threatened with the increasing number of residents every year which causes the demand for residential land and infrastructure to increase. In addition to harvested area, consumption per capita of the population of North Sumatra is also a factor that affects food security in North Sumatra. The condition of harvested areas in North Sumatra is increasingly threatened with the increasing number of residents every year which causes the demand for residential land and infrastructure to increase. In addition to harvested area, consumption per capita of the population of North Sumatra is also a factor that affects food security in North Sumatra